Lost and now found : explorers, diplomats and artists in Egypt and the near East - Cooke, Neil, 1947-; Daubney, Vanessa, (ASTENE and Archaeopress Publishing Ltd., 2017)
Long distance travel and mass tourism are not recent phenomena. This collection of papers from the 2015 ASTENE Conference in Exeter demonstrates that over the centuries many individuals and groups of people have left the safety of their family home and travelled huge distances both for adventure and to learn more about other peoples and places. Some travels were to help establish trade routes, while others were for personal pleasure and knowledge. Many of those who travelled have left little or no record but in a few cases their travels can be determined from the brief encounters they had with other travellers who noted these chance meetings in their journals and diaries, which they later used to inform and write for publication accounts of their own travels and impressions.